WHAT DETERMINANTS INFLUENCE STUDENTS TO START THEIR BUSINESS? EMPIRICAL EVIDENCE FROM UNIVERSITAS PANCASILA - Aulia Keiko Hubbansyah; Nurul Hilmiyah; Derriawan (FEB-UP Press, 2023)
This study aims to identify determinants in influencing students' decision to become entrepreneurs. Seven indicators were employed in order to investigate which determinants that has bigger effect on student’s decision. Those indicators are (1) parents' work, (2) household expenses, (3) entrepreneurial orientation, (4) attitudes towards risk, (5) innovation ability, (6) perceptions of financial difficulties, and (7) university support. 100 students in faculty of economics and business Universitas Pancasila were chosen as samples to be empirically tested using a series of questionnaire’s questions. Logistic regression technique was applied to obtained targeted results. The results revealed that all the seven analyzed variables shown positive and significant effects on students' intention to become entrepreneurs. Moreover, parent's job (POT) is shown as the most influencing determinant followed by Entrepreneurship orientation (OKW) and perception of financial difficulties (PKK). Accordingly, this research contributes practically how to develop student’s intention effectively to become entrepreneur where family and environment factors are the main determinants.